O comércio eletrônico e a proteção do consumidor no Direito Brasileiro - Moreira, Tatiana Artioli (2016)
The subject of this study is to investigate the e-commerce, and the protection of the consumer in the Brazilian law. Thus, it intends to analyze the consumer virtual relationships, and the consumer rights in such digital environment, as well as, briefly discuss, the study of the Project of Law from the Senate, no. 281/2012, that updates the Consumer Defense Code, including e-commerce provisions. Therefore, this work is a study of a theoretical nature and focused on bibliographic research and standards governing trade on the Internet. As an introduction, this work presents the rise of the consumer society and the evolution to the information society, as a result of the technological transformations of the latest decades. From the analysis of the beginning of the Internet and its evolution in Brazil, we evolve to discuss about the e-commerce, the contributions and controversies arising from such business model, and, the traits of the e-commerce consumer contracts. Thereafter, an overview of the consumer protection laws applicable to the e-commerce is presented, with focus on the UNCITRAL and European Directive in the international scale, and in the national scenario, the Brazilian Consumer Code, the E-Commerce Decree and the Internet Civil Mark in Brazil, laws that aim at the protection of the consumers. With such overview, the study finds grounds to discuss about the rights of the consumers inserted in the virtual commerce, the principles that should guide the actions of the suppliers and some commercial practices most commonly used in the virtual environment to reach the consumer and offer products and services. The result of this study points out that, regardless of the existence of rules for protection of consumers and establishment of guidelines for suppliers in the e-commerce environment, it is necessary to provide specific rules to regulate the consumer relations in such environments, in consideration of its specificities